2021
DOI: 10.1088/1674-1056/abdb22
|View full text |Cite
|
Sign up to set email alerts
|

Tuning transport coefficients of monolayer MoSi2N4 with biaxial strain*

Abstract: Experimentally synthesized MoSi2N4 (Science 369 670 (2020)) is a piezoelectric semiconductor. Here, we systematically study the large biaxial (isotropic) strain effects (0.90–1.10) on electronic structures and transport coefficients of monolayer MoSi2N4 by density functional theory (DFT). With a/a 0 from 0.90 to 1.10, the energy band gap firstly increases, and then decreases, which is due to transformation of conduction band minimum (CBM). Calculated results show that the M… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 42 publications
1
21
0
Order By: Relevance
“…1(c and d) show the band structure, density of states (DOS), and partial DOS (PDOS) of MoSiN nanosheet, indicating that it is a semiconductor with an indirect bandgap (E g ) of 1.74 eV with the valence band maximum (VBM) and conduction band minimum (CBM) located at the G and K points, respectively. The calculated band structure and DOS/PDOS spectra and bandgaps agree well with the previous theoretical reports 31,37,38 and with the experimental bandgap (1.94 eV). 27 The bandgap calculated with the hybrid functional (HSE06) is 2.35 eV, 27 higher than the experimental value.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…1(c and d) show the band structure, density of states (DOS), and partial DOS (PDOS) of MoSiN nanosheet, indicating that it is a semiconductor with an indirect bandgap (E g ) of 1.74 eV with the valence band maximum (VBM) and conduction band minimum (CBM) located at the G and K points, respectively. The calculated band structure and DOS/PDOS spectra and bandgaps agree well with the previous theoretical reports 31,37,38 and with the experimental bandgap (1.94 eV). 27 The bandgap calculated with the hybrid functional (HSE06) is 2.35 eV, 27 higher than the experimental value.…”
Section: Resultssupporting
confidence: 90%
“…29 This made MoSiN the focus of intensive research aiming to uncover its novel properties. [30][31][32][33][34][35][36][37][38][39] Following the successful MoSiN preparation, many MX 2 Y 4 (M = Cr, V, Mo, W, Ta; X = Si, Ge; and Y = N, As, P) monolayers have been studied. 40,41 It was found that WSi 2 N 4 , CrSi 2 N 4 , and MoSi 2 N 4 monolayers have the highest piezoelectric coefficients as compared with the other known 2D materials.…”
mentioning
confidence: 99%
“…The moderate band gap, high mobility, and excellent stability of monolayer MoSi 2 N 4 promise its advantages in nano-electronic and optoelectronics. Since the experimental synthesis of layered MoSi 2 N 4 , an enormous amount of research efforts have been devoted to exploring its various properties [17][18][19][20][21][22][23][24][25][26][27]. Density functional theory (DFT) calculations indicated that monolayer MoSi 2 N 4 has a larger Poisson's ratio (0.28) [17] than that of graphene (0.16) [28].…”
Section: Introductionmentioning
confidence: 99%
“…According to figure 2, it is obvious from the chart that the mobile phone market in China each year had an extremely big enhancement which reached peak in 2016, despite a small amount decrease in 2017. [6]But overall, the surge of the whole mobile phone market is in this also means that consumers can more easily buy a reasonable price and accept the mobile phone . With the support of the mobile phone market, Tencent gradually launched Wechat, the software, and added more novel functions such as: WeChat Pay, Mini Programs, and Game Center are very popular among consumers.…”
Section: Figure 2 China's Smartphone Market Amountmentioning
confidence: 99%